Prototype of IoT-Based Fruit Alcohol Level Measurement Tool - Nursila, Nursila; Ilham, Dirja Nur; Yunan, Amsar; Harahap, Muhammad Khoiruddin; Candra, Rudi Arif (Yayasan Cita Cendekiawan Al Khwarizmi, 2021)
The effect of alcohol on health is very large if you consume too much, and the fact that excessive alcohol levels can interfere with digestion can cause eye function disorders, decreased brain and nerve function as well as cancer. Knowing the alcohol content in fruits that are suitable for consumption by the body from an early age is very important. Based on this problem, this study aims to create a prototype measuring instrument for the alcohol content of fruits using the Blynk application. This circuit consists of 3 circuits, namely the input part in the form of an Mq3 sensor, the control part in the form of Nodemcu, and the output port in the form of the Blynk application. From the results of testing tools for four samples including durian, grapes, papaya, and apples for 25 times the test of the fruit is peeled for the next 2 hours the average percentage of durian alcohol content is 28.57%, grapes are 12.68%, papaya is 5.79 %, and apples by 18.6%. In this study, there is also the notification facility to the third smartphone that the alcohol content exceeds the alcohol content which is not good from the value set on the device.